Aging and Directed Forgetting: Evidence for an Associative Deficit but No Evidence for an Inhibition Deficit. - Tanberg, Pelin; Fernandes, Myra A.; MacLeod, Colin M. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2022)
Intentional forgetting aims to prevent unwanted information from being stored in long-term memory. Surprisingly, past research has shown that, relative to younger adults, older adults recall and recognize more to-be-forgotten information. It has been suggested that this occurs because older adults have a deficient ability to inhibit information. In two experiments, we examined memory differences between older and younger adults in an item-method directed forgetting task. Participants viewed words one at a time during a study phase, each followed by a cue to remember (R) or to forget (F). In Experiment 1, participants' later recognition of both types of items was assessed, followed by a separate source discrimination test for the cue that had been associated with each word at study. In Experiment 2, memory was assessed using a threeresponse recognition test, indicating whether each word was either new or previously studied and, if previously studied, whether it was associated with an R cue or an F cue. In both experiments, older and younger adults recognized more to-be-remembered items than to-be-forgotten items, the typical directed forgetting effect (DFE). Contrary to past reports, older adults did not remember more to-be-forgotten items than did younger adults, inconsistent with an inhibitory deficit. Older adults were, however, less accurate than younger adults in identifying cue associations for both R and F items, consistent instead with an associative memory deficit.